Philippines Success in Improving Birth Registration - World Bank; Philippines Statistics Authority (World Bank, Washington, DC, 2017)
Civil registration is the continuous, permanent, and compulsory recording of vital events and the civil status of persons and of modification of the records. A vital event is an event which has to do with an individual’s entrance into or departure from life together with any change in civil status which may occur during an individual’s lifetime. For births that occurred outside a health facility, the attendant at birth, which can be the traditional birth attendant (hilot), has the responsibility to prepare the certificate of live birth (COLB). The parents must make sure that the COLB is registered with the Local Civil Registry Offices (LCRO) within the reglementary period of 30 days. In the absence of a hospital and clinic administrator or attendant at birth, either or both parents of the child shall register the birth. When the birth occurs aboard a vehicle, vessel, or airplane while in transit, registration of said birth shall be a joint responsibility of the driver, captain, or pilot, as the case may be, and the parents.